Uma nova forma de ser igreja: redes globais de relacionamento e crise denominacional entre Batistas Nacionais (1990-2020) - SANTOS, Lyndon de Araújo (2022)
A phenomenon that has drawn the attention of Brazilian research over the decades, the national evangelical question – the form it involves in a game of exchanges, positions and assimilations – the latest denominations of our training. Using the Igreja Batista do Angelim as a smaller scale and starting point, we intend to shed light on the connection that exists between some global networks of relationships and an alleged denominational crisis – also global. Thus, it addresses questions related to its extra national elements, objective questions to questions, questions that, from the beginning the question, guides the analysis. At first, it understands the history of the IBA from the account of its two pastors-leaders, exploring the instrumentalization of this small biographical history within the great history that is Christianity in contemporary times, its transformations and its ruptures, playing between the place, the Church Batista do Angelim, and the global. In the second chapter, we will try to avoid an effort in, which would be to define what the evangelical is in Brazil, we go off the tangent of these generalities to, in fact, try to understand who is the evangelical that the IBA intends to form, bibliographically ecclesiastical manuals that the institution and use it for your disciples. That is why, having defined the history of this church within the history of Christianity, the church is what is evangelical and inappropriate and whoever is a Brazilian evangelical, is so called to show how an end look, which prevails in academics, would not understand our object of study altogether – in our understanding likewise, it does not understand the contemporary evangelical in the most adequate way.